London clubland : - Milne-Smith, Amy, 1977- (Palgrave Macmillan, 2011)
"In this first academic history of the famed gentlemen's clubs of London, Amy Milne-Smith reveals these institutions at the height of their power and influence at the turn of the twentieth century, paying special attention to how clubmen defined masculinity and status for their generation. Based on extensive research in club archives along with newspapers, journals, diaries and memoirs, Milne-Smith takes us behind the majestic doors of these most exclusive clubs. Readers will find London Clubland not only an engaging account of clubs, but also a story of troubled marriage, contested urban space, shifting boundaries of class, and a robust masculine culture in decline"-- Από τον εκδότη.